Critical thinking : conceptual perspectives and practical guidelines - Dwyer, Christopher P. (Cambridge : Cambridge University Press, 2017)
Dwyer's book is unique and distinctive as it presents and discusses a modern conceptualization of critical thinking - one that is commensurate with the exponential increase in the annual output of knowledge. The abilities of navigating new knowledge outputs, engaging in enquiry and constructively solving problems are not only important in academic contexts, but are also essential life skills. Speci{uFB01}cally, the book provides a modern, detailed, accessible and integrative model of critical thinking that accounts for critical thinking sub-skills and real-world applications; and is commensurate with the standards of twenty-first-century knowledge. The book provides both opportunities to learn and apply these skills through a series of exercises, as well as guidelines on how critical thinking can be developed and practised, in light of existing psychological research, which can be used to enhance the experience of critical thinking training and facilitate gains in critical thinking ability.
Title from publisher's bibliographic system (viewed on 25 May 2017).
Keywords: Critical thinking; Logic; Reasoning